Barrier Options Model for Agricultural Commodity Price Protection - Gilang Primajati; M Najib Rodhi; Adrian Juniarta Hidayat (Jurnal Varian, 2020)
Application of barrier options for determining insurance premiums for agricultural commodity prices due to lower selling prices by applying certain barrier levels. In determining the price of insurance premiums for agricultural commodity prices such as rice, the price is assumed to follow the Brown Geometric Motion and for the determination of the barrier level line the researcher uses the Brown Bridge Motion so that there is a relationship between Bridge and Barrier. In conclusion, we obtain a model to determine the number of insurance premiums. The barrier option model approach is used to construct a fairer formula for insurance premiums on agricultural commodity prices.